Inovasi Bahan Ajar Berbasis Kontekstual Untuk Meningkatkan Hasil Belajar Pada Pokok Bahasan Hidrolisis Garam Di SMA - Sry Nur Afrida; Marudut Sinaga (Universitas Negeri Medan, 2019)
This study aims to (1) obtain high school-based chemical teaching material products based on salt hydrolysis materials that are in accordance with BSNP standards (2) find out whether the learning outcomes of students taught using innovative teaching materials are higher than the learning outcomes taught without the use of innovative teaching materials .The feasibility of the contents 3.63, the feasibility of 3.58 languages, the feasibility of presenting 3.56, and the feasibility of graphics 3.72, average pre-test score ofn 3 3, 2 5 and the average post-test score was 79.63. Hypothesis testing firstly conducted a normality test that is equal to 9.49 <11.07 in the experimental class 9.64 <11.07 in the normally distributed control class, the results of the analysis of the normality test in the control and experimental class amounted to 1.15569 <1.582 namely data on both classes are normal, the results of the hypothesis test that is the right hand side test, the table is obtained with α = 0.05 and db = n-1 = 40-1 = 39 which is 1.6671 and t arithmetic = 2.20192 means the increase in learning outcomes taught using innovative teaching materials is greater than using regular teaching materials